Insights on innovation: Charting trends in digital education through a novel hybrid AI-human coding methodology - Grogan-Graham, Erika; Byers Reid, Tracy; Hughes, Janette; Petrarca, Diana (Proceedings of the International Conference on Networked Learning, 2026)
Digital innovation in education is rapidly evolving. The purpose of this paper is to explore the insights and relevant themes highlighted by a group of educational researchers and practitioners from a digital innovation educational conference. The inaugural conference, hosted in April 2025 by the Centre for Digital Innovation in Education, invited submissions to share and discuss current topics in education innovation. Presenters submitted proposals in line with our four conference themes: 1) Pedagogical Innovation, 2) Structural Innovation, 3) Digital Innovation, and 4) Teaching for Innovation. As a site for networked learning, the hybrid online and in-person format supported connections and a shared sense of challenge among presenters and attendees. The session formats (i.e., keynote speakers, paper presentations, workshops, round tables, posters, social networking event, and graduate student luncheon) fostered conversations around contemporary themes in innovative educational practices in both formal and informal capacities. As a social practice, the conference enabled educators, researchers and students to formulate digital and social connections that contributed to broadening their professional communities within the professional development ecology. For the purpose of this content analysis, conference submissions refer to topic summaries from invited guest speakers (n=5) and confirmed proposals (n=46). We conducted a content analysis of the conference submissions (n=51) by coding the data through three different processes: ATLAS.ti and Open AI, Data Analysis by ChatGPT, and human-centred coding. This process leveraged AI to assist with refining and confirming coding. Our three-stage, iterative approach explores qualitative coding through a purpose-built application, an open-source platform, and a human-centred process to improve reliability when using emerging technology. Analysis of the 51 conference submissions revealed the following themes: integration of technology in learning; culturally relevant pedagogy; leveraging digital technologies to foster social and emotional learning (SEL) competencies; digital pedagogy and innovative instructional design; challenges of accessibility and inclusivity; AI and ethical considerations; innovative assessment practices; and faculty development and institutional readiness for digital innovation integration. Our paper offers two significant contributions to educational research: 1) it highlights the current topics and issues that educators and researchers perceive as innovative, relevant and transformative in the area of digital education; and 2) it describes an innovative methodological approach, along with its challenges, of using AI for qualitatively coding conference proposals.